İlköğretim dönemi (7-8 yaş) çocuklarında resim-iş derslerinde hikaye üretmenin resim becerilerine etkisinin araştırılması - Abut, Melek (My University, 2005)
Araştırmanın amacı hikaye üretmenin ilköğretim 1.sınıf (7-8 yaş) çocukların resim becerilerine etkisini araştırmaktır. Deney ve kontrol gruplu ön test-son test ölçümlerine dayanan deneysel desenli bir çalışma olan araştırmada; bağımsız değişken olarak belirlenen hikâye üretme yönteminin, bağımlı değişken olan resim becerileri ( biçimsel yaratıcılık, anlamsal yaratıcılık, orijinallik ve görsel algı) üzerindeki etkisi araştırılmıştır. Araştırmanın çalışma grubunu İstanbul'daki bir okuldan toplam 26 çocuk (13 deney,13 kontrol olmak üzere) oluşturmuştur. Ön-test aşamasında çocuklara her biri üç sözcükten oluşan kelime grupları ( 5 tane) verilmiş ve bu kelime grupları ile ilgili resim yapmaları istenmiştir. Deneysel çalışma safhasında deney grubu çocuklardan bu kelime grupları ile ilgili hikâye üretmeleri istenmiştir. Daha sonra ise son-test aşamasında hem deney hem de kontrol grubundan bu kelime grupları ile ilgili tekrar resim yapmaları istenmiştir. Çocukların ön-test ve son-test resimleri üç sanat uzmanından oluşan bir değerlendirme ekibi tarafından puanlanmıştır.

The aim of this research was to investigate the effect of story writing on art skills (formal creativity, semantic creativity, originality and visual perception) on first grade (7-8years old) children. The research was designed in experimental model which was based on pre-test and post-test with experimental and control groups. The effects of independent variable-story writing- on dependent variable- art skills were examined. The subjects were consisted of 26 children (13 experimental;13 control) from an elementary school in Istanbul. All of the children were asked to make pictures of each given three word groups (each consisted three familiar words) for pre-test phase. During the application of the method, children of the experimental group were asked to produce stories from given word groups and than they asked to make pictures for each word groups for post test phase, while control group were not asked to produce stories, just asked to make pictures for each word groups at pre and post test phases. In determination of the effectiveness of the story writing, the pre and post test samples were evaluated by three art instructors. After application and collection of the data, statistical analyses were made to determine the effectiveness of the story writing on art skills. According of the results, there were no differences between experimental and control groups in terms of art skills before the story writing phase. However experimental group had significantly high scores than control group on post-test results. So this method can be recommended for teachers to apply for 7-8 years old children in art course.
Keywords: Resim Becerileri, İlköğretimde; Resim-İş Öğretmenliği; Sanat Eğitimi; Yaratıcı sanatlar ve el sanatları; Yaratıcılık, Sanatta